URGENSI PENEGAKAN HUKUM TATA PEMERINTAHAN - Murtir Jeddawi (Jurnal Pallangga Praja (JPP), 2020)
Global pandemic, Corona Virus must be prevented, limited and be stopped of spreading to the whole of Indonesian region. As a nation state based on law (regulation) all of government’s activities are limited include of activities which aim to pulfill order and welfare of society There are many instruments could be held it, and one of it, implementation of the governance principle, such as transparancy, efficiency, accountability etc. For supporting it, government law has strong roling to implementing those principles. Besides it, with the government law (bestuursrecht) provided limitation of governemnt authority and protected for the society by the government misused of authority. Therefore, central government issued regulations. Those regulation are government law (bestuursrecht).